2010
DOI: 10.1021/jf1008692
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics and Antioxidant Properties of Fruit Pulp and Cell Wall Fractions of Postharvest Banana (Musa acuminata Juss.) Cultivars

Abstract: Banana fruits are important foods, but there have been very few studies evaluating the phenolics associated with their cell walls. In the present study, (+) catechin, gallocatechin, and (-) epicatechin, as well as condensed tannins, were detected in the soluble extract of the fruit pulp; neither soluble anthocyanidins nor anthocyanins were present. In the soluble cell wall fraction, two hydroxycinnamic acid derivatives were predominant, whereas in the insoluble cell wall fraction, the anthocyanidin delphinidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 38 publications
10
54
2
Order By: Relevance
“…The unripe banana flours from 75 to 105 days had a significantly higher level of TPC (3.23-3.48 mg GAEg −1 ) while TPC from flour of banana 120 days was reduced to 2.59 mg GAEg −1 . The concentration of TPC in this study was slightly different compared with the report of (Bennett et al, 2010), who found that the TPC of banana (Terra cultivar) was 6.50-9.90 mgg −1 . This may due to the variation of varieties, growing season, postharvest treatment and growing management.…”
Section: Antioxidant Activitiescontrasting
confidence: 99%
See 1 more Smart Citation
“…The unripe banana flours from 75 to 105 days had a significantly higher level of TPC (3.23-3.48 mg GAEg −1 ) while TPC from flour of banana 120 days was reduced to 2.59 mg GAEg −1 . The concentration of TPC in this study was slightly different compared with the report of (Bennett et al, 2010), who found that the TPC of banana (Terra cultivar) was 6.50-9.90 mgg −1 . This may due to the variation of varieties, growing season, postharvest treatment and growing management.…”
Section: Antioxidant Activitiescontrasting
confidence: 99%
“…The total acidity, pH and reducing sugar of green banana flour in this study were comparable to that studied by Bennett et al (2010). The starch is converted to sugars as the banana fruit starts to ripen.…”
Section: Discussionsupporting
confidence: 75%
“…FFA value of sunfl ower oil supplemented with unripe banana peel extracts, BHA and α-tocopherol under accelerated storage at 65°C for 24 days. Different letters within each storage period denote that they are signifi cantly different (p < 0.05) (Bennett et al, 2010;Lim et al, 1997;Sulaiman et al, 2011). However, literature on the phytochemical profi les of the peel and pulp of bananas is still scarce and inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…A high level of resistant starch in the RRP (20.8 ± 1.9, n = 3, - Table 2) appears to be a possible reason for the observed low GI. Nevertheless, this is not conclusive because of the presence of other food components in the food matrix such as fibre [27], polyphenols [28] and cell wall and/or components [29]. Further investigations on the possible reasons for the observed low GI of ripe raw plantain are therefore required.…”
Section: Discussionmentioning
confidence: 99%